The University of Mississippi : A Sesquicentennial History - Sansing, David G. (Book collections on Project MUSE., 1999)
"There is a mystique about Ole Miss," David G. Sansing says in his new book The University of Mississippi: A Sesquicentennial History (University Press of Mississippi, cloth 37.00). Sansing, a professor emeritus of history, says the University and its story hold a special attraction for those who have learned there. "Some have called it holy ground, others hallowed ground. During a recent Black Alumni Reunion Danny Covington called Ole Miss addictive." Few Southern institutions have such a storied past. After its founding, the University assembled one of the finest scientific collections in.